Aramid fibers reinforced silica aerogel composites with low thermal conductivity and improved mechanical performance. (May 2016) - Li, Zhi; Cheng, Xudong; He, Song; Shi, Xiaojing; Gong, Lunlun; Zhang, Heping
Abstract: Aramid fibers reinforced silica aerogel composites (AF/aerogels) for thermal insulation were prepared successfully under ambient pressure drying. The microstructure showed that the aramid fibers were inlaid in the aerogel matrix, acting as the supporting skeletons, to strengthen the aerogel matrix. FTIR revealed AF/aerogels was physical combination between aramid fibers and aerogel matrix without chemical bonds. The as prepared AF/aerogels possessed extremely low thermal conductivity of 0.0227 ± 0.0007 W m −1 K −1 with the fiber content ranging from 1.5% to 6.6%. Due to the softness, low density and remarkable mechanical strength of aramid fibers and the layered structure of the fiber distribution, the AF/aerogels presented nice elasticity and flexibility. TG–DSC indicated the thermal stability reaching approximately 290 °C, can meet the general usage conditions, which was mainly depended on the pure silica aerogels. From mentioned above, AF/aerogels present huge application prospects in heat preservation field, especially in piping insulation.